Identifikasi Sumber Stres Tenaga Pengajar Dan Pengaruhnya Terhadap Kinerja Dosen Di STIE Widya Gama Lumajang - Budiwati, Hesti (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2016)
This study aims to identify the sources of stress that affect the performance faculty lecturer at STIE Widya Gama Lumajang and to obtain empirical evidence on the effect of the source of significant stress teaching staff partially and simultaneously on the performance of STIE Widya Gama Lecturer in Lumajang. The results of this study are expected to contribute to the management and Lecturers STIE Widya Gama Lumajang. This study measured the stress source faculty comprised of tasks, roles, conflicts between departments, remuneration and recognition, occupation or profession and measure its effect on the performance of Lecturer. The study population was Lecturer in STIE Widya Gama Lumajang, and taken a sample of 30 lecturers from the Department of Management and Accounting. Data were analyzed using multiple linear regression analysis. Hypothesis testing is done partially and simultaneously. The results showed that in partial assignments, conflicts between departments, remuneration and recognition, occupation or profession. While the role tidka variables affect the performance of lecturers. Simultaneously source of stress lecturer significant effect on performance. The coefficient of determination (R square) of 0.418 or 41.8% mean stress variables faculty able to explain its influence to change the performance variables and the remaining 58.2% is explained by other variables. Further research is expected to contribute in the development of management science studies, especially human resource management in a college environment, so it can be a reference for similar research and advanced research.